An Overview of The Role of Tumor Necrosis Factor-Alpha in Epileptogenesis and Its Terapeutic Implications. - Michev, Alexandre; Orsini , Alessandro; Santi , Viola; Bassanese, Francesco; Veraldi , Daniele; Brambilla , Ilaria; Marseglia, Gian Luigi; Savasta, Salvatore; Foiadelli, Thomas (Acta Biomedica Atenei Parmensis, 2022)
The complex association between neuroinflammation and seizures has been widely investigated in recent years. As mediators of inflammatory response, cytokines like tumor necrosis factor-a (TNF-a) are potential therapeutic targets for epileptic disorders. TNF-a is a pleiotropic cytokine with a controversial role in epileptogenesis, seemingly capable to both favor the genesis of seizures and elicit neuromodulatory responses. Anti-TNF agents are a group of monoclonal antibodies engineered to inhibit the response to this cytokine for antinflammatory purposes. The clinical experience of the use of these drugs in neurological conditions like multiple sclerosis showed controversial results. Evidence in favor of the employment of anti-TNF agents for the treatment of epilepsy are still limited to certain forms of disorders, notably Rasmussen encephalitis, and in carefully selected patients.